1965
DOI: 10.2118/1011-pa
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Equilibrium in Porous Materials

Abstract: The experimental points which describe capillary pressure curves are determined at apparent equilibria which are observed after hydrodynamic flow has ceased. For most systems, the time required to obtain equalization of pressure throughout the discontinuous part of a phase is prohibitive. To permit experimental points to be described as equilibria, a model of capillary behavior is proposed where mass transfer is restricted to bulk fluid flow. Model capillary pressure curves follow if the path described by such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 0 publications
8
73
0
Order By: Relevance
“…4 result from u = constant − H (S w ), where the constant is defined by the intersection point with ∂H im or ∂H dr . The hysteretic function H obtained this way gives a close match to the experiments of Morrow and Harris (1965). Having explicit expressions for P im and P dr , for instance the van Genuchten expressions, would result in a (semi) explicit expression for H .…”
Section: Extended Playtype Hysteresis Modelsupporting
confidence: 63%
See 3 more Smart Citations
“…4 result from u = constant − H (S w ), where the constant is defined by the intersection point with ∂H im or ∂H dr . The hysteretic function H obtained this way gives a close match to the experiments of Morrow and Harris (1965). Having explicit expressions for P im and P dr , for instance the van Genuchten expressions, would result in a (semi) explicit expression for H .…”
Section: Extended Playtype Hysteresis Modelsupporting
confidence: 63%
“…Moreover, condition (2.7) ensures that scanning curves originating from arbitrary points on ∂H im or ∂H dr remain in H. The question arises how to choose and construct a function H that gives scanning curves close to experimental data and satisfies (2.7) for mathematical consistency. We present a construction that is based on the experiments of Morrow and Harris (1965). Their results for drying and wetting are shown in Fig.…”
Section: Extended Playtype Hysteresis Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Poulovassilis (1962Poulovassilis ( , 1970a found a good agreement between the predicted and the measured scanning curves for glass beads and sand. Other investigators reported considerable discrepancies between the theory and observations; Topp and Miller (1966), Morrow and Harris (1965), and Bomba and Miller (1967) observed discrepancies for glass-beads medium; Vachaud and Thony (1971), Talsma (1970), and Poulovassilis and Childs (1971) observed them for sand; Topp (1969Topp ( , 1971a observed them for various loam soils. It seems that the measured discrepancies are due partly to the method of measurement because the poorest agreement between theory and measurements has been observed for unsteady-flow experiments.…”
Section: Theory Of Capillary Hysteresismentioning
confidence: 95%